Rural women: an annotated Caribbean bibliography with special reference to Jamaica - Instituto Interamericano de Ciencias Agrícolas (IICA) (Instituto Interamericano de Ciencias Agrícolas (IICA), 2020)
The bibliography is divided into three sections. Section A is comprised of publications covering the theoretical framework and international context of women in development. Section B is an attempt at extracting those that seem most relevant to the understanding of rural Jamaican women and their environment. Section C is a general compilation of writings concerning Jamaican women, with entries further divided into sub-categories and cross-referenced. This is followed by a special listing of publications available from the Jamaican Women's Bureau, and an alphabetical author index. Special attention has been given to listing works available in Jamaica; almost all of the publications and papers cited can be found at the National Library, Institute of Jamaica, at the University of the West Indies, at the United Nations Library in Kingston, or at the Jamaica Women's Bureau. For those interested in acquiring additional information on women and development, Development As If Women Mattered: An Annotated Bibliography with a Third World Focus, edited by May Rihani and published under the auspices of the Secretariat for Women and Development of the New Transcentury Foundation, is an excellent source of documents.